Effects of Laser‐Scribed Mo Groove Shape on Highly Efficient Zn(O, S)‐Based Cu(In, Ga)Se2 Solar Modules. Issue 4 (29th January 2020) - Li, Jianmin; Niu, Jiabin; Wu, Xiao; Kong, Yifan; Gao, Jinlong; Zhu, Jiakuan; Li, Qiang; Huang, Lan; Wang, Shijin; Chi, Zheng; Xiao, Xudong
Abstract : In this work, the effects of the Mo groove (P1 line) shape on the quality and performance of final modules are investigated. A gradual sloped Mo edge is successfully realized by controlling the laser beam parameters and incidence directions. As a comparison, a sharp vertical Mo edge is also investigated. With the traditional sharp vertical groove shape, voids, cracks, and peel‐offs near the abrupt step edge of P1 lines are often found to grow within the Cu(In, Ga)Se2 (CIGS) layer and induce unwanted growth behavior of the transparent conducting oxide (TCO) layer. With the sloped groove shape, conformal growth with a continuous surface for CIGS, Zn(O, S) buffer, and Al:ZnO TCO layers without cracks and peel‐offs at the P1 position from the ablated glass region to the pristine Mo region is successfully realized. The suppression of voids, cracks, and peel‐offs in the CIGS layer effectively reduces the number of shunting pathways for the solar modules and helps to greatly improve the fill factor and efficiency of Zn(O, S)‐based CIGS modules. Finally, a Zn(O, S)‐based CIGS module of 16.3% efficiency is obtained with a cell width of 7 mm after use of MgF2 antireflective coating. Abstract : Effects of laser‐scribed Mo groove shape on Zn(O, S)‐based Cu(In, Ga)Se2 (CIGS) solar modules are investigated. A gradual sloped Mo groove scribed with a laser beam in the P1 process is critical in influencing the subsequent growth of other functional layers in the CIGS module and improves the module performance, especially for the fill factor.